Determining Factors of Customer Satisfaction and Repurchase Intention Of Madura Store Customers In Surabaya: The Role of Service Quality and Perceived Value - Damis Veri Budianto; Sudarmiatin Sudarmiatin; Heri Pratikto (Greenation Research & Yayasan Global Resarch National, 2026)
This study examines the influence of service quality and perceived value on customer satisfaction and loyalty at Madura Stores in Surabaya. Competition in the retail industry, both traditional and modern, is increasingly fierce. The challenge is not simply knowing, liking, and enjoying the store, but also how to maintain repeat purchase intentions among customers at Madura Stores in Surabaya. Data collection was conducted through an online survey distributed using Google Forms, using a structured questionnaire as the instrument. The data collection method used a questionnaire. Data analysis in this study used a structural equation model (SEM) using PLS 3.0. Data collection used a survey and 148 participants were distributed via Google Forms. The results show that service quality and perceived value have a positive and significant effect on customer satisfaction, which in turn significantly impacts customer loyalty.